VELOCITY ESTIMATION FOR PORE-PRESSURE PREDICTION - Bell D.W. (My University, 2004)
The speed of propagation of compressional-wave energy in the subsurface, known simply as "formation velocity," is strongly influenced by compaction, particularly in young clastic basins. Because pore pressures affect compaction, changes in velocity can be calibrated to changes in pore pressure. Velocities derived from surface seismic data provide indirect pressure measurements at undrilled locations. The accuracy depends on the validity of the relationship between pressure and velocity, the quality of the velocity measurements at enough points to perform the calibration and prediction, and the reliability of average velocities to correctly convert from seismic time to depth. A key step is construction of a velocity profile with depth that simultaneously defines both the compaction characteristics and a valid time-depth curve. A linear fit to the logarithm of the sonic transit time with depth is commonly assumed to represent the normal compaction trend. Such a velocity-depth trend, however, does not produce a time-depth relationship that accurately converts seismic measurements in time to depth. A linear fit of velocity with time provides a consistent fit to both time-depth and velocity-depth data and is a better empirical representation of the normal compaction trend. The linear velocity-time model can be used to smooth through inaccuracies in seismic stacking-velocity picks where applied to geologically consistent units. This chapter illustrates relationships between velocity and the geologic setting and establishes an empirical model for the normal compaction trend. It then reviews various assumptions and techniques for converting seismic stacking velocities into representative formation velocities. It concludes with a step-by-step recommendation for estimation and calibration of velocity from seismic data.